PENGARUH PENGETAHUAN PERPAJAKAN, TAX MORALE, KEPERCAYAAN KEPADA PEMERINTAH, DAN TEKNOLOGI INFORMASI PERPAJAKAN TERHADAP TAX EVASION (Studi Kasus Wajib Pajak Orang Pribadi UMKM di Kabupaten Pemalang) - Aqilah Melani Putri; Nur Cahyonowati (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the influence of tax knowledge, tax morale, trust in the government, and tax information technology on tax evasion among individual taxpayers in micro, small, and medium enterprises (MSMEs) in Pemalang Regency. This study used the Theory of Planned Behavior approach. The variables which are used in this study consist of tax knowledge, tax morale, trust in government, tax information technology, and tax evasion. The sampling technique used was purposive sampling, utilizing data collection methods that combine online questionnaires via Google Forms and offline questionnaires using physical forms. The sample size was determined using the Hair et al. (2010) formula, amounting to 155 respondents. The research data was processed using multiple linear regression analysis with IBM SPSS 26 program. The results of this study found that tax knowledge, tax morale, and trust in government had a significant negative effect on tax evasion, while tax information technology did not have a significant effect on tax evasion.